Secrets of a beautiful woman; R. Tjandrapradja’s "Wawacan rusiah nu geulis": a morality tale from West Java - Mukherjee, Wendy (Wacana, Journal of the Humanities of Indonesia, 2025)
Raden Tjandra Pradja’s Wawacan rusiah nu geulis (The verse tale of the secrets of a beautiful woman) which was published in 1921 is a verse narrative of high literary merit. A tale of sexual morality, it is an early example of the realist fiction which was to develop during the first half of the twentieth century in the Sundanese language of West Java. The work carries an unusual and intricately woven sub-text telling of ethnic and cultural tension in Bandung, the provincial capital, through the representation of non-Sundanese figures – Hadhrami Arabs and cosmopolitan foreign Muslims. An Arab, Sheikh Abubakar bin Ma’rup al-Attas is made the villain of the piece. A community of Indians and emigres from Palembang, Sumatra, is further portrayed, according to stereotypes of the time, as wealthy merchants, strict in their observance of Islam but uncultivated in the Western-educated ways of the Sundanese elite. There is a historical irony lying behind this sub-text, since at the time of the work’s appearance progress was underway within the Hadhrami community of the Indies in the matter of religious reform, inspired by the ideas of Muhammad Abduh of Egypt. Furthermore, in 1923, in Bandung itself, members of the resident Palembang community and a Tamil Muslim from Singapore were to find the Persatuan Islam (Islamic Association) an organization which, through its pamphlets, lectures, and public debates was to create an intellectual vanguard of reformist thought in West Java.